Education, immigration and migration : policy, leadership and praxis for a changing world - Arar, Khalid; Brooks, Jeffrey S.; Bogotch, Ira (Emerald Publishing Limited, 2019)
Global Migration has changed the practice of educational leaders, policy makers, students, teachers and community members. This book traces this worldwide shift through research-based chapters that touch on both local idiosyncrasies and dynamics common across many contexts.Education, Immigration and Migration identifies issues educational leaders face as they seek to lead schools and school systems experiencing immigration and better understand their current strategies for improvement. The chapters shed light on the poorly understood relationship between educational leadership and refugee populations by giving a deeper appreciation of the scope and nature of issues at local, national and transnational levels. Each chapter offers new ways in which practitioners, policy-makers and scholars can think about complex dilemmas such as the implementation of equitable and democratic values, and difficulties involved in adapting organization and culture. Given its cross-national interdisciplinary approach, this book will prove invaluable for educational leaders, scholars and policymakers alike.
Includes index.
Keywords: Immigrant children -- Education.; Refugee children -- Education.; Education -- Educational Policy & Reform -- General.; Organization & management of education.; elektronické knihy; electronic books